Model Pembuatan Peraturan Daerah Berbasis Syariat Islam (Perspektif Legislative Drafting Kontemporer) - Jazim Hamidi (Jurnal Hukum IUS QUIA IUSTUM, 2003)
The alternative model of Producing Local Regulation (PERDA) which are based on Islamic Laws constitutes a new, urgent concept in the context of legislative draffing renewal. Because the process of producing the regulations (from the planning unto its soccialization/evaluation) must follow the principles of generating good and democratic laws, it must also accommodate Islamic values and principles. While the word "Islamic Laws" can be understood both inclusively and exclusively.